Perception of Seed technology Training among Farm Women - Shobhana Gupta , K. L. Dangi and Shilpi Verma, (Indian Journal of Extension Education, 2015)
In the present stud, farmwomen's perception about the importance, need and adequacy of seed technology trainingconducted in two different KVKs of Rajasthan state was evaluated. Atotal of 120 farmwomen were randomly selected forthe study. Data were collected through interview schedule. Results reveal that training on use of seed culture was found tobe most important and training in new improved seed production technology was needed utmost in future to increase theproduction. Training on depth of sowing was found to be most adequate amomg majority of the respondents. Thus, farmwomen needed better training in some areas of seed technology and seed treatment. Therefore, there is a need to organizetraining programmes to stimulate higher participation of farmwomen in seed production so that women become moreeconomically independent and improve financial status of the family